Alcoholic liver disease is a strong predictor of colorectal polyps in liver transplant recipients - Ma, Ann T.; Therrien, Amélie; Giard, Jeanne-Marie; von Renteln, Daniel; Bouin, Mickael (Endoscopy International Open, 2017)
Background and aims Colorectal cancer (CRC) is associated with a significantly reduced survival rate in transplant recipients. The prevalence and risk factors of CRC and of colorectal polyps after orthotopic liver transplant (OLT) remain unclear. The study aim was to determine the prevalence of colorectal polyps in OLT recipients. A secondary objective was to explore possible risk factors of polyps.Patients and materials This was a retrospective single center study of all OLT recipients transplanted between 2007 and 2009. All patients who underwent a colonoscopy 5 ± 5 years after OLT were included. The outcome was colorectal polyps, as identified on colonoscopy. A logistic regression model was performed to identify potential predictors of polyps.Results Of 164 OLT recipients, 80 were included in this study. Polyps were diagnosed in 37 % of patients before transplant and in 33 % afterwards. With regard to post-transplant lesions, 22 % were advanced adenomas or cancerous. In the regression analysis, the odds of post-transplant polyps were 11 times higher in patients with alcoholic liver disease (OR 11.3, 95 %CI 3.2 – 39.4; P < 0.001).Conclusion Patients with end-stage liver disease may be at high risk of colorectal polyps before and after liver transplant, and screening should be continued in both contexts. Those with alcoholic liver disease are particularly at risk for post-OLT polyps and may benefit from more intensive screening.